Programmable logic controller based variable speed drives for educational trainer - Chin, Ken Leong (2013)
The PLC based motor control system is the key area of concerned to relate PLC to the real industrial environment. However, there is no PLC based industrial motor control trainer available in the Automation lab of Politeknik Kota Kinabalu for the practical purposes. This has initiated the need to develop a research and product on the title of “Programmable Logic Controller Based Variable Speed Drives For Educational Trainer”. This research focused on VSD controlled by PLC conventional programming and Fuzzy Logic based PLC programming. A prototype “Two Conveyors Packaging System” has been constructed. This application is to synchronize two conveyors so that parts and packaging boxes are positioned correctly, regardless of the part and package box positions and the speed of conveyor. Several PLC programs were developed individually for sectionals of the prototype application; the input devices photoelectric part sensors (P004A), motor encoders E1 and E2 (P004B) and output device is VSD for box conveyor M2 (P004E). All these programs can work independently; subsequently to be combined to control the whole prototype application with additional PLC program on conventional basis, and fuzzy logic basis (P004C and P004D). These step by step programming methods contributed to the 10 experiments procedures to achieve the objective to construct the educational trainer procedures. As a conclusion, this research has achieved the objectives to construct the educational trainer procedures to implement PLC conventional and fuzzy logic based programming to control a motor driven by VSD, based on the concept of Prototype Two Conveyor Packaging System.